A dual-port MIMO antenna system for 5G and Wi-Fi 6E communications using a parasitic element - Aziz Dkiouak; Faouzi Rahmani; Mohssine El Ouahabi; Alia Zakriti; Mostafa Baghouri; Anass El Mamouni (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
The increasing demand for high-speed, reliable wireless communication necessitates innovative antenna designs that can efficiently support emerging technologies such as 5G and Wi-Fi 6E. Traditional antenna solutions often struggle to meet the compactness, isolation, and efficiency requirements posed by these advanced systems. This research addresses these challenges by introducing a compact dual-hook multiple input multiple output (MIMO) antenna specifically tailored for 5G and Wi-Fi 6E applications. The proposed antenna offers dual-band operation in a small size with high isolation at both resonance frequencies (3.6 GHz and 7.1 GHz). The novel design has a simple and low-profile structure and can be easily integrated into practical applications. It reduces the cost and complexity of the system. The MIMO technology has a good reflection coefficient, a good efficiency and a maximum gain of 3.85 dB. To enhance the effeciency of this structure, parasitic element and defective ground structure (DGS) are combined. The twin-hook radiators are printed symmetrically on the top layer of low-cost FR-4 substrate with a small size of 19 × 36 mm2 (0.23 λ0 × 0.45 λ0, with λ0 is the guided wavelength at the lowest operating frequency). In addition, the DGS is formed by cutting two symmetrical slots into the semi-ground plane to provide better impedance matching at both resonant frequencies. Based on the simulation findings, the -10 dB return loss bandwidth of the proposed structure reaches approximately 14,08% and 10,21% for 3.6 GHz and 7.1 GHz, respectfully. On the other hand, high isolation is obtained, reaching over -21 dB in the low frequency band and -29 dB in the high frequency band. Also, for verification of MIMO system characteristics, diversity gain (DG), envelope correlation coefficient (ECC), total active reflection coefficient (TARC) and channel capacity loss (CCL) are analysed and used to investigate the proposed MIMO antenna diversity performance.